CARACTERIZACIÓN DE LA CAPACIDAD FUNCIONAL Y CINEANTROPOMÉTRICA DE LOS DEPORTISTAS DEL DEPARTAMENTO DEL HUILA (Fiep Bulletin - online, 2016)
The study aimed to determine the functional characteristics and kinanthropometric of Athletes from different sports leagues Huila Department. It was a transversal study, in which they took 100% of the population (618 athletes) assigned to 18 performance of Huila Sports Leagues (468 male, 75.7% and 150 women, 24.3%). To find the functional capacity of the athletes performed the following tests: Endurance Cardiovascular (VO2max), indirect laboratory testing according treadmill (American College of Sports Medicine - ACSM, 2001), power was applied jump test Vertical (test of "Sargent" and Lewis formula) (Hatze, 1998); Flexibility test Wells (Sit and Reach) (Wells & Dillon, 1952), resistance abdominal muscles - 1min Abs test (ACSM, 2000) . Regarding cinentropométricas characteristics were used measurement techniques recommended by the International Society for the Advancement of Cineantropometría (International Society for the Advancement of Kinanthropometry - ISAK, 2001), registering a total of 20 measures. Data were purified and analyzed in SPSS 17 on Windows XP environment, was held at first a univariate descriptive analysis, then proceeded to inference analysis in which Anova tests were performed using Fisher's statistic and post-tests of Sheffey hot in this sense, will work with the confidence level of 95%, considering rejection condition of independence between variables that the p-value was less than 0.05. The results showed significant differences between groups of sports offered by the Institute for Recreation and Sport (IDRD) in Sports Performance Project (2004), gender and athletes taken as reference.
Keywords: Functional capacity; kinanthropometry; fitness.